Solving higher order ordinary differential equations using parallel 2-point explicit bock method - Omar, Zurni; Suleiman, Mohamed (Jabatan Matematik Universiti Teknologi Malaysia, 2005)
The derivation of a new parallel 2-point explicit block (2PEB) method for solving dth order ordinary differential equations (ODEs) directly is made. Computational advantages are presented comparing the results obtained by he new method with that of conventional 1-point method. Numerical results suggest that the parallel 2PEB method is recommended for solving second order ODEs directly using finer step sizes.